Reading Rem Koolhaas - Bart Verschaffel (Architectural Histories, 2013)
This article was written for a symposium organized on the occasion of the honorary doctorate granted to Rem Koolhaas by the Vrije Universiteit Amsterdam on October 19, 2012. It discusses the metaphors of time Koolhaas uses and its implications for understanding architecture.